ANTIOXIDANT ACTIVITY LEAVES KATIMAHA (Kleinhovia hospita L.) - Nova Elda Utami; Salni Salni; Marieska Verawaty (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2022)
The free radicals that people face in their daily activities require humans to get additional antioxidants from the outside. To overcome this problem, it is necessary to look for many sources of natural antioxidants considering the need for antioxidants that are increasingly needed Katimaha (K. hospita L.) is believed to have many benefits in the field of medicine. Therefore, katimaha has the potential to be used as a source of natural antioxidants. The research methods carried out were refining katimaha leaf simplicia, extraction, fractionation, antioxidant activity test with TLC plate, purification, determination of compound class, and antioxidant activity test using the DPPH method. The results showed that the active fraction of Katimaha leaf was the n-hexane fraction and the ethyl acetate fraction. Column chromatography on the active fraction found six pure eluates that had antioxidant activity, namely N1, N3, N5, E1, E2, and E4. Groups of compounds N1, N3, N5, E1 are terpenoids, group E2 eluates are tannins, while E3 eluates are flavonoid compounds. The pure eluate antioxidant activity test using the DPPH method obtained IC50 values of N1 are 40,142 ppm, N3 80,057 ppm, N5 271,643 ppm and E1 89,16 ppm, E2 124.91 ppm and E4 52.51 ppm.